Visualization and identification of single meteoritic organic molecules by atomic force microscopy. (1st February 2022) - Kaiser, Katharina; Schulz, Fabian; Maillard, Julien F.; Hermann, Felix; Pozo, Iago; Peña, Diego; Cleaves, H. James; Burton, Aaron S.; Danger, Gregoire; Afonso, Carlos; Sandford, Scott; Gross, Leo
Abstract: Using high‐resolution atomic force microscopy (AFM) with CO‐functionalized tips, we atomically resolved individual molecules from Murchison meteorite samples. We analyzed powdered Murchison meteorite material directly, as well as processed extracts that we prepared to facilitate characterization by AFM. From the untreated Murchison sample, we resolved very few molecules, as the sample contained mostly small molecules that could not be identified by AFM. By contrast, using a procedure based on several trituration and extraction steps with organic solvents, we isolated a fraction enriched in larger organic compounds. The treatment increased the fraction of molecules that could be resolved by AFM, allowing us to identify organic constituents and molecular moieties, such as polycyclic aromatic hydrocarbons and aliphatic chains. The AFM measurements are complemented by high‐resolution mass spectrometry analysis of Murchison fractions. We provide a proof of principle that AFM can be used to image and identify individual organic molecules from meteorites and propose a method for extracting and preparing meteorite samples for their investigation by AFM. We discuss the challenges and prospects of this approach to study extraterrestrial samples based on single‐molecule identification.